GUIDO'S SACRIFICE IN LIFE IS BEAUTIFUL BY ROBERTO BENINGNI (1997): A HUMANISTIC PSYCHOLOGICAL APPROACH - Adinda, Adinda (2011)
The researcher employs the descriptive as a type of research. The researcher data sources are divided into two, namely primary data source and secondary data source. The primary data source is the Life is Beautiful movie released in 19997. While the secondary data source are other materials taken from some books of humanistic, biography of the director, website about the film and another data related to this research. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusion. First, based on the structural analysis it is evident that in this Life is Beautiful, Roberto Benigni as Guido and also as the major character in this film is trying hard to solve his sufferings with many creative way. All of the aspects in this movie support each other, from the characters, mise-en-scene, lighting, cinematography, sound and editing that make a beautiful unity in the movie. Second, based on the humanistic psychological analysis, there is close relation between the movie production and the underlying theory which reflected that a person from lower class like Guido Orefice can satisfy his needs to survive and solve the problem of his life with the unique way. Being powerless can make people creative is a message that is shown in this movie.